2017
DOI: 10.1002/2016gl072045
|View full text |Cite
|
Sign up to set email alerts
|

Stick‐slip dynamics of flow‐induced seismicity on rate and state faults

Abstract: Changes in pore pressure due to the injection or extraction of fluids from underground formations may induce potentially damaging earthquakes and/or increase the sensitivity of injection sites to remote triggering. The basic mechanism behind injection‐induced seismicity is a change in effective stress that weakens a preexisting fault. The seismic potential of a given fault is controlled by the partitioning between seismic and aseismic slip events, which emerge as a manifestation of stick‐slip instabilities. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 61 publications
1
30
0
Order By: Relevance
“…We point out that former model, motivated by fracture stimulation in tight reservoirs, assumed fluid perturbations only within the fault and is less appropriate for general fluid-induced earthquakes; additionally, it is the fault pressure rather than the fault poroelastic stress that is passed from the fluid problem to the solid problem, so the model is essentially fluid-to-solid decoupled. Recently, applications to induced seismicity of the former were reported by, for example, Gischig (2015) and Norbeck and Horne (2016) and of the latter model by Juanes et al (2016) and Cueto-Felgueroso et al (2017).…”
Section: 1029/2018jb015669mentioning
confidence: 99%
“…We point out that former model, motivated by fracture stimulation in tight reservoirs, assumed fluid perturbations only within the fault and is less appropriate for general fluid-induced earthquakes; additionally, it is the fault pressure rather than the fault poroelastic stress that is passed from the fluid problem to the solid problem, so the model is essentially fluid-to-solid decoupled. Recently, applications to induced seismicity of the former were reported by, for example, Gischig (2015) and Norbeck and Horne (2016) and of the latter model by Juanes et al (2016) and Cueto-Felgueroso et al (2017).…”
Section: 1029/2018jb015669mentioning
confidence: 99%
“…In our context, radiation damping acts as a velocity-dependent cohesion that caps the maximum slip velocities. Quasi-dynamic simulations of induced earthquake sequences in poroelastic media with rate-and-state faults were first presented in (Cueto-Felgueroso et al, 2017). It has been suggested that smaller radiation damping terms in the quasi-dynamic models can lead to results similar to those computed with dynamic models (Lapusta & Liu, 2009;Lapusta et al, 2000;Thomas et al, 2014).…”
Section: Quasi-dynamic Approach To Modeling Rupturesmentioning
confidence: 99%
“…We present, for the first time, dynamic simulations of ruptures in rate-and-state faults in poroelastic media. Hydromechanical simulation, coupling single-phase or multiphase flow with geomechanics through the Biot theory of poroelasticity (Biot, 1941;Rice & Cleary, 1976), has recently emerged as a key technology to assess the impact of flow processes on induced earthquakes (e.g., Cappa & Rutqvist, 2011a, 2011bCueto-Felgueroso et al, 2017;Jha & Juanes, 2014;McClure & Horne, 2011;Rinaldi et al, 2014). Most analyses of flow-induced earthquakes based on fully coupled modeling have focused so far on fault reactivation-the onset of slip.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we discuss the quasi‐dynamic simulations of unstable fault slip using fully coupled hydromechanical simulations and rate‐and‐state friction laws. Our simulations are quasi‐dynamic in the sense that we assume quasi‐static equilibrium in the rock mechanical response, with radiation damping to guarantee bounded slip velocities (Cueto‐Felgueroso et al, ; Pampillon et al, ; Rice, ; Thomas et al, ). The relevance of using rate‐and‐state friction is that reactivation, earthquake nucleation—the transition to unstable slip—and rupture propagation can be simulated in a unified framework, which is the basic building block needed for simulations of the full earthquake cycle in poroelastic media.…”
Section: Introductionmentioning
confidence: 99%
“…Capturing these processes requires simulations that are well‐resolved in space and time. We have previously used the proposed modeling framework to simulate the impact of rate‐and‐state model parameters on earthquake sequences (Cueto‐Felgueroso et al, ), and to characterize the impact of viscoelastic damping on dynamic ruptures in poroleastic media (Pampillon et al, ). Two features of our numerical model that allow an accurate resolution of the poroelastic and frictional processes during rupture are the use of monolithic coupling with adaptive time stepping and the robustness of the frictional contact algorithm.…”
Section: Introductionmentioning
confidence: 99%